Construindo o pertencimento afroquilombola através das contribuições da pretagogia no Quilombo De Serra do Juá – Caucaia/Ce - Silva, Cláudia de Oliveira da (2016)
This research took place from the need to expand the meanings of afroquilombola belonging to contribute to the empowerment of the people of Sierra Jua community, from the construction path of my blackness. The field of research was the quilombo Serra do Jua, which had the participation of 15 co-investigators (as) in the period 2013 to 2015. To find out how people experience the feeling of belonging, culture and African ancestry, making relationship with their histories, trajectories and reference places in your life, I have formulated the following questions: As markers of Africanities, worked by Pretagogia may allow the appropriation of elements that contribute to the strengthening of afroquilombola belonging? As the Sociopoética can contribute to the empowerment of bodies and collective memory for approaching the themes of africandiades? These questions led me to discover potentiating information for the community to have more engagement in the struggles and resistances. The main authors I used were: Jacques Gauthier (2012) with the theme of poetics, which needed to introduce techniques for unlocking the bodies and individual and collective memory; Petit (2015) on the Pretagogia and markers of Africanities, which brought the main contribution to the production of knowledge, Semedo (2010), with the riches of the Guinean Comb cloth, and Silva (2013) on experiences with pretagógicas practices classroom, which gave me concrete evidence of use of this methodology, among others (as) that were fundamental to my readings and conclusions. I found that the afroquilombola belonging is a broad concept of senses and meanings. People demonstrated interaction, because before the work they had remained silent, timidly and after the workshops began to express more will, through various languages, oral and body, expressing the sense of belonging. Thus, I conclude that Pretagogia and Sociopoética were protagonists in the assumption of positive attitudes / co-researchers / the.